Випускники кадетських корпусів – активні учасники Українських визвольних змагань 1917–1921 рр. - Ткачук, А. (Україна: культурна спадщина, національна свідомість, державність, 2009)
In article were shown the life and service of graduating students of cadet schools in Ukrainian military formations in 1917–1921.